Gasochromic response of optical sensing platform integrated with polyaniline and poly(3,4-ethylenedioxythiophene) exposed to NH3 gas - Ismail, Abdul Hadi; Mohd Yahya, Nor Akmar; Mahdi, Mohd Adzir; Yaacob, Mohd Hanif; Sulaiman, Yusran (Elsevier, 2020)
The optical NH3 gas sensing performance of polyaniline (PANI) and poly(3,4-ethylenedioxythiophene (PEDOT) in the form of bilayers and copolymers was analysed in this study. The order of the bilayers and the presence of acid dopant on the fabrication of the sensing platform produced different absorbance responses upon exposure to NH3 gas. The limit of detection of the bilayer (PANI(aq.)/PEDOT(aq.)) was 7.86 ppm which is under the threshold limit value of NH3, with response and recovery times of 2.33 min and 46.8 s, respectively. The gasochromic behaviour of PANI and PEDOT during the adsorption of NH3 gas was closely related to the changes in the oxidation state which have simultaneously altered the colour intensity of the respective sensing layer.